Electric Fencing - Prakash, Mahendra; Sarwal, Shiam S. (Indian Forester, 1958)
An electric fencing was tried at Jodhpur, Rajasthan, by the Desert Afforestation and Soil Conservation Station and was found to be considerably cheaper and effective as compared to other types of fencing. The article describes the equipment required, its erection and details of subsequent maintenance, etc. Comparative costs of different kinds of fencing and their advantages and disadvantages have also been described.